Efektivitas Metode Eksperimen Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA Materi Perubahan Wujud Benda Kelas IV MI Ma’arif Sutawinangun Kabupaten Cirebon - Permatasari, Fitri; Al Ghozali, Muhammad Iqbal; Shulkhah, Shulkhah; Purwati, Ratna (LJPI UI Bunga Bangsa Cirebon, 2022)
This study discusses the Effectiveness of Experimental Methods on Student Learning Outcomes in Science Subjects Material Changes in Forms of Objects in Class IV MI Ma'arif Sutawinangun Cirebon Regency Year. The study was motivated by teachers who were less creative when choosing the right learning method, at the time of learning the teacher only provided conventional methods with continuous care and rarely used experimental methods for science subjects so that there was a lack of enthusiasm and student activity in the learning process, which affected the learning process. student learning outcomes are still less than optimal. This study aims to determine the learning outcomes of the control class students who were taught without using the experimental method and the experimental class that was taught using the experimental method. And to find out whether the experimental method is effective in improving the learning outcomes of fourth grade students of MI Ma'arif Sutawinangun. This research is a type of quantitative research using the experimental method of this research model, namely the posttest-only control design. The population of this study was the fourth grade students of MI Ma'arif Sutawinangun, the number of which was 52 students divided into 2 classes, namely the control class and the experimental class. Researchers used observation instruments, multiple choice questions and documentation, in data management used descriptive data analysis and hypothesis testing analysis. The results of data analysis using descriptive statistics through experimental methods on the learning outcomes of fourth grade students of MI Ma'arif Sutawinangun are effective. This can be shown through hypothesis testing independent sample t-test, the value of tcount is 2.811 > ttable, which is 2.007. So from these results it can be seen that the experimental method is effective in improving the learning outcomes of fourth grade students of MI Ma'arif Sutawinangun. In other words, this hypothesis is accepted. The application of the experimental method is expected to illustrate that the learning method does not always use the lecture method. With the experimental method, it is hoped that students will be more active and creative in the learning process so that they can improve the learning outcomes of fourth grade students of MI Ma'arif Sutawinangun. Abstrak Penelitian ini membahas Efektivitas Metode Eksperimen Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA Materi Perubahan Wujud Benda Kelas IV MI Ma’arif Sutawinangun Kabupaten Cirebon Tahun. Kajiannya dilatar belakangi oleh guru yang kurang kreatif pada saat memilih metode pembelajaran yang tepat, pada saat pembelajaran guru hanya memberikan metode konvensional dengan terus menurus dan jarang sekali menggunakan metode eksperimen untuk mata pelajaran IPA sehingga kurangnya antusias serta keaktifan siswa dalam proses pembelajaran, yang berpengaruh pada hasil belajar siswa yang masih kurang maksimal. Penelitian ini bertujuan untuk mengetahui hasil belajar siswa kelas kontrol yang di ajar tanpa menggunakan metode eksperimen dan kelas eksperimen yang di ajar menggunakan metode eksperimen. Serta untuk mengetahui apakah metode eksperimen efektif dalam meningkatkan hasil belajar siswa kelas IV MI Ma’arif Sutawinangun. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan metode eksperimen model penelitian ini yaitu posttest-only control design. Populasi penelitian ini adalah siswa kelas IV MI Ma’arif Sutawinangun yang jumlahnya 52 siswa yang terbagi dalam 2 kelas yaitu kelas kontrol dan kelas eksperimen. Peneliti menggunakan instrumen Observasi, tes soal pilihan ganda dan dokumentasi, dalam pengelolaan data digunakan analisis data deskrptif serta analisis uji hipotesis. Hasil analisis data dengan menggunakan statistik deskriptif melalui metode eksperimen terhadap hasil belajar siswa kelas IV MI Ma’arif Sutawinangun ini efektif. Hal ini dapat ditunjukkan melalui uji hipotesis uji independent sampel t-test diperoleh nilai thitung yaitu 2,811 > ttabel yaitu 2,007. Sehingga dari hasil ini dapat di ketahui bahwa metode eksperimen efektif dalam meningkatkan hasil belajar siswa kelas IV MI Ma’arif Sutawinangun. Dimana dengan kata lain hipotesis ini diterima. Penerapan metode eksperimen diharapkan dapat memberi gambaran bahwa metode pembelajaran tidak selalu menggunakan metode ceramah. Dengan adanya metode eksperimen di harapkan siswa lebih aktif dan kreatif dalam proses pembelajaran sehingga dapat meningkatkan hasil belajar siswa kelas IV MI Ma’arif Sutawinangun.